Seekers of Secret Worlds in Finland’s Early Twentieth Century Literature - Parente-Čapková, Viola (Elephant & Castle, 2019)
In my article, I look at Finland’s early twentieth century literature, concentrating on the work of two writers, L. Onerva (1882-1972) and Eino Leino (1878-1926) from the point of view of modern Western esotericism. As the central notion, I employ the concept of seekership, used lately by Nina Kokkinen vis à vis visual arts. The concept proves most viable when analysing E. Leino’s and L. Onerva’s literary œuvre and the mélange of esoteric, mystic, occult, spiritualist, theosophical and other trends. I give some background to the trend of seekership in Finland’s literature around the turn of the 19th and the 20th century, concentrating mostly on Leino’s work and considering the interaction of the “little” and “great” traditions, i. e. the local tradition of Finnish mythology as manifested in the folk poetry, and the tradition of European literature. In the latter section of the paper, I discuss L. Onerva’s work from the perspective of seekership, concentrating on her ways of gendering the figure of the seeker. My research enters in dialogue with the recent research on esotericism in Finnish cultural history, namely the current project Seekers of the New.